2020
DOI: 10.1002/cti2.1176
|View full text |Cite
|
Sign up to set email alerts
|

Disease extent and anti‐tubercular treatment response correlates with Mycobacterium tuberculosis‐specific CD4 T‐cell phenotype regardless of HIV‐1 status

Abstract: Objectives. The development of non-sputum-based assays for tuberculosis (TB) diagnosis and treatment monitoring is a key priority. Recent data indicate that whole blood-based assays to assess the phenotype of Mycobacterium tuberculosis (Mtb)-specific CD4 T cells hold promise for this purpose and require further investigation in well-characterised TB cohorts. In this study, we investigated the relationship between the phenotypic signature of Mtb-specific CD4 responses, TB disease extent and treatment response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 49 publications
6
54
1
Order By: Relevance
“…Finally, we showed that of all the immunological features that were different between recent and remote M.tb infection, T cell activation was the best biomarker for differentiating between infection states. Overall, the T cell activation biomarker appears very robust, regardless of mycobacterial antigen specificity (M.tb lysate or CFP-10/ESAT-6) or the assay used for detection (PBMC-ICS, tetramer staining or, as previously reported, whole blood stimulation [17] , [18] , [19] , [20] , [21] , [22] ). This study focused on understanding T cell immunobiology during acquisition of M.tb infection and the discovery of potential biomarkers to distinguish between recent and remote M.tb infection.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Finally, we showed that of all the immunological features that were different between recent and remote M.tb infection, T cell activation was the best biomarker for differentiating between infection states. Overall, the T cell activation biomarker appears very robust, regardless of mycobacterial antigen specificity (M.tb lysate or CFP-10/ESAT-6) or the assay used for detection (PBMC-ICS, tetramer staining or, as previously reported, whole blood stimulation [17] , [18] , [19] , [20] , [21] , [22] ). This study focused on understanding T cell immunobiology during acquisition of M.tb infection and the discovery of potential biomarkers to distinguish between recent and remote M.tb infection.…”
Section: Discussionsupporting
confidence: 53%
“…Expression of HLA-DR, a member of the MHC class II family typically expressed by antigen-presenting cells, is often used as a marker of T cell activation [ 15 , 16 ]. In the context of tuberculosis, studies have shown that disease, regardless of HIV status, is associated with significantly higher levels of T cell activation than M.tb infection, and that activation is reduced upon successful antimicrobial treatment [17] , [18] , [19] , [20] , [21] , [22] . These studies suggest that antigen-specific T cell activation could be used as a biomarker of microbial burden, and potentially infer in vivo antigen exposure during different stages of infection and disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of HLA-DR, a member of the MHC class II family typically expressed by antigen-presenting cells, is often used as a marker of T cell activation [15,16]. In the context of tuberculosis, studies have shown that disease, regardless of HIV status, is associated with significantly higher levels of T cell activation than M.tb infection, and that activation is reduced upon successful antimicrobial treatment [17][18][19][20][21][22]. These studies suggest that antigen-specific T cell activation could be used as a biomarker of microbial burden, and potentially infer in vivo antigen exposure during different stages of infection and disease.…”
Section: Introductionmentioning
confidence: 99%
“…TST and IGRAs have a low predictive value for tuberculosis [26]. Other functional assays that measure M.tbspecific T cell properties such as Th1 cytokine co-expression profiles [27,28], T cell differentiation (CD27, [29,30]) and T cell activation [17][18][19][20][21][22] have been proposed as new potential immunodiagnostic concepts that can distinguish between M.tb infection and disease. In line with this principle, potential biomarkers of recent M.tb infection based on proportions of TNF-only (IFN--IL-2-) TE (CD45RA-CCR7-CD127-) CD4 T cells or T cell proliferation, as well as a blood transcriptomic signature, have been described [31][32][33].…”
Section: Introductionmentioning
confidence: 99%